SIPPO TRADE PROMOTION PROGRAMME OF OSEC FOR MEDICINAL AND AROMATIC PLANTS - Staubli, F.; Duerbeck, K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Innumerable medicinal plants grow in the mountains and tropical rain forests of many Asian, African and Latin American countries. Many are barely investigated and their active ingredients are not yet known. They are of interest for the pharmaceutical industry and show great potential for the ever-growing health food market. For emerging markets and countries in transition, medicinal plants represent an opportunity to harvest their national resources in a sustainable manner. It is therefore of utmost importance to harvest, process and transport the medical herbs in a way that preserves the maximum amount of their active ingredients. The increasing demand for wild collected products in the sectors of food, personal health care and medicinal herbs poses major ecological and social challenges. That’s why SIPPO initiated the development of a new FairWild standard. We focus on companies from 14 partner countries that offer medicinal herbs, functional or pharmaceutical food products, are ready for the international market, preferably have some export experience, produce according to international quality standards, offer products marketable in Switzerland and the European Union, are motivated and dedicated to deal with new markets, and have a representative in the company who has a sufficient command of the English language. SIPPO Swiss Import Promotion Programme is a mandate from the State Secretariat for Economic Affairs of Switzerland (SECO), carried out by Osec. The programme supports small and medium-sized enterprises (SME) from emerging markets and markets in transition to access the Swiss and European markets.